Mobile Internet Usage Possibilities and Requirement in Agriculture - Szilágyi, Róbert (Acta Agraria Debreceniensis, 2005)
In this paper, I looked at the mobile Internet from technological, economical and sociological aspects and then pointed to several agricultural possibilities for theri usage. Examining the effects and driving forces of mobile communication, I can say that it is a very complex system. The social connections of mobile communication and the arising problems show that it affects several areas of everyday life. By looking at the business processes, all costs, advantages and disadvantages can be seen clearly. Overview the mobile Internet from the technological aspect and I discuss related technology and applicable utilities, as well as two possibilities for using wireless Internet: 3G and WiFi. Among the possible usages, I gave several examples to give an impression of all the diverse possibilities this technology offers. There are some really useful applications in customer service, precision farming, transport, agriculture and food industry. Finally, I talked about the mobile Internet in Hungary and in the other EU countries.